The Impact of Student Activeness in the Independent Campus Learning Program (MBKM) on Students' Readiness to Enter the World of Work - Irbi Damayanti Matondang; Riyan Ashari Silalahi; Marlya Fatira Ak (Universitas Serambi Mekkah, 2024)
This research aims to determine the impact of student activity in the Independent Campus Learning Program (MBKM) on students' readiness to enter the world of work and evaluate the effect of the Independent Campus Learning Program (MBKM) on the Medan State Polytechnic campus. This evaluation was conducted using a questionnaire for Medan State Polytechnic students who had or are currently taking part in the 2021-2023 Independent Campus Learning (MBKM) program. To achieve this primary goal, implementing the MBKM Program includes eight learning activities: student exchange, independent internships, teaching campuses, research/research, humanitarian projects, entrepreneurial activities, independent studies/projects, and thematic real-work lectures. The research results show that implementing the MBKM Program impacts several things, namely increasing experiential learning to shape students' hard skills and soft skills in the world of work and fulfilling graduates' learning outcomes. The results of this research also show that the MBKM program provides considerable benefits in terms of competency for Medan State Polytechnic students. Not only does it benefit students, the Independent Campus Learning Program (MBKM) also positively impacts parties involved with students in carrying out the Independent Campus Learning Program (MBKM) and increasing students' knowledge and skills. The MBKM program also affects students' readiness to enter the world of work, especially Polmed students who have participated in the MBKM program in the field of internship/field practice. Apart from that, this research also identified the satisfaction of Medan State Polytechnic students with the MBKM program implemented by the KEMENDIKBUDRISTEK and Medan State Polytechnic.Keywords: MBKM, Competency, World of Work, Understanding